A highly stable and sensitive GO-XDA-Mn2O3 electrochemical sensor for simultaneous electrooxidation of paracetamol and ascorbic acid. (10th August 2017) - Ejaz, Ammara; Jeon, Seungwon
Graphical abstract: Highlights: π–π interaction of graphene oxide (GO) with 1, 4-xylenediamine (XDA) was studied. The synergistic effect of the Mn2 O3 nanospheres with GO-XDA was electrochemically studied in the detection of Paracetamol (PCT) and ascorbic acid (AA). The GO-XDA-Mn2 O3 accurately detected PCT and AA with LOD of 5.6 × 10 −8  M and 6.0 × 10 −7  M respectively. The GO-XDA-Mn2 O3 selectively detected PCT and AA simultaneously in the presence of DA, 5-HT and Glu with peak separation of 240 mV. Abstract: Highly stable electrochemical sensor based on strong π- π interactions between GO and XDA was fabricated for simultaneous as well as for individual detection of paracetamol (PCT) and ascorbic acid (AA). The oxidation potential of PCT and AA was greatly resolved with the decoration of Mn2 O3 nanospheres. We believe that, presence of metal oxide on the surface of GO-XDA will offer higher electrochemical performance with its large surface area and fast electron transfer ability. Therefore, a comparative study was executed in the presence and absence of Mn2 O3 nanospheres on the surface of GO-XDA. The GO-XDA-Mn2 O3 modified electrode showed electrocatalytic oxidation of PCT in a very wide linear range of 1 × 10 −6 –1 × 10 −3  M with limit of detection (LOD) and sensitivity of 5.6 × 10 −8  M, 527.04 μAmM −1 cm −2 respectively and AA with 1 × 10 −5 –8 × 10 −3  M linear range, LOD and sensitivity of 6.0 × 10 −7  M, 655.74 μAmM −1 cm −2 respectively. Furthermore, astonishing stability was found when GO-XDA-Mn2 O3 nanocomposite was stored for over a week. The proposed sensor displayed incredible selectivity, sensitivity and excellent recovery results for real samples with appreciable consistency and precision suggesting practical utility of the GO-XDA-Mn2 O3 as an effective and reliable electrochemical sensor for simultaneous as well as individual determination of PCT and AA.